SIFAT FISIKA BAMBU GALAH (Gigantochloa atter) BERDASARKAN ARAH AKSIAL DI KECAMATAN GUNUNG SARI KABUPATEN LOMBOK BARAT: Effects of Axial Directions to the Physical Properties of Galah Bamboo(Gigantochloa atter) in Gunung Sari Region, Western Lombok Regent - Andi Tri Lestari; Febriana Tri Wulandari (PERENNIAL, 2020)
Lombok island is one of the islands in Indonesia which is rich in bamboo varieties and one of them is galah (Gigantochloa atter). This species is generally used for crafting and furniture by people of the Gunung Sari area, Western Lombok Regent. The study of the physical properties of this bamboo was important because they were correlated to bamboo quality especially for cutting, defects, boring, shaping, stripping, and sanding. The objective of this study was to understand the influence of axial directions (bottom, middle, and top portions) on physical properties and their values which were investigated with the experimental method. The experimental design was completed randomized design (CRD) employing axial directions as the parameters with three replications. The statistical analyses were Anova with range tests at α = 5%, and Least Significant Difference (LSD) tests at α = 5%. The results showed that the treatments of physical properties (axial directions at the bottom, middle, and top portions) of galah bamboo were not significantly different. The average fresh moisture content was 176.21%, air-dried moisture content 14.43%; fresh density 0.40; air-dried density 0.54; oven-dried density 0.51.Keywords: axial directions; density; galah bamboo; moisture content; physical properties